2021
DOI: 10.1016/j.jcmgh.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fructose Alters the Composition, Localization, and Metabolism of Gut Microbiota in Association With Worsening Colitis

Abstract: The incidence of inflammatory bowel diseases is increasing worldwide, suggesting a potential role for dietary factors. Here, we demonstrate that a high fructose diet worsens colitis in a microbiota-dependent manner. Overall, this study highlights the importance of diet-microbe interactions in intestinal inflammation. BACKGROUND & AIMS: The incidence of inflammatory bowel diseases has increased over the last half century, suggesting a role for dietary factors. Fructose consumption has increased in recent years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 63 publications
3
59
0
Order By: Relevance
“…This experiment revealed that HSD microbiota induced immune cell redistribution, but did not aggravate DSS-induced colitis. This is an interesting finding because we transferred high-sucrose-associated microbiota, while two other studies using microbiota from high-fructose-or high-glucose-fed mice showed increased severity of colitis in exGF mice [33,34].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This experiment revealed that HSD microbiota induced immune cell redistribution, but did not aggravate DSS-induced colitis. This is an interesting finding because we transferred high-sucrose-associated microbiota, while two other studies using microbiota from high-fructose-or high-glucose-fed mice showed increased severity of colitis in exGF mice [33,34].…”
Section: Discussionmentioning
confidence: 80%
“…Colitis in HSD-fed mice was associated with pronounced weight reduction and infiltration of neutrophils into colon, together with increased levels of pro-inflammatory cytokines. Increased susceptibility to colitis has been also observed in other studies in mice fed with high-fructose [18,[32][33][34], high-glucose [18,34], or high-sucrose diets [17,34]. Unfortunately, none of these studies followed the effect of HSD in the model of chronic colitis, which allows to study repeated remissions and relapses typical for ulcerative colitis [54].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Desai and colleagues demonstrated that fed a low-fibre diet, the gut microbiota in mice resorted to mucus layer glycoproteins as a nutrient source, leading to erosion of the colonic mucus barrier, which serves as a primary defence against enteric pathogens [56]. When [34,35] Reduces risk of flares [59] Improves disease activity [60] FODMAPs Fermented by commensal bacteria in distal gut to produce gas and distension [62] Exclusion improves symptoms [63,65] Exclusion improves symptoms [63,65] Wheat/Gluten ATI proteins stimulate release of inflammatory cytokines, activate Toll-Like Receptors and induce a T-Cell response [69,70] Improved symptoms, especially in stricturing CD [71][72][73] Improved symptoms [71][72][73] Sugar Increased gut permeability Decreased microbial diversity Increased pro-inflammatory cytokines [66,67] Restriction improved clinical indices and mucosal healing in a small paediatric study [101] Reported by patients but no trials to support [21] Fat Saturated fat>increased taurine conjugation of hepatic bile acids>increases sulphate reducing microorganisms>promote pro-inflammatory T-cell response [102][103][104] n-3 PUFA anti-inflammatory vs. n-6 PUFA pro-inflammatory [105][106][107] Higher n-3 PUFA: n-6 PUFA ratio improves remission rates [108] High dietary fat intake [78], in particular myristic acid (found in palm oil, coconut oil and dairy fat) associated with flares [109] Emulsifiers Erode mucus barrier [110] Increase translocation of invasive E. Coli [111] Increase pro-inflammatory cytokines [110] No studies in humans No studies in humans Nanop...…”
Section: Dietary Fibrementioning
confidence: 99%